Molecular Identification of Sarcocystis sp. (Apicomplexa, Sarcocystidae) in Offspring of Tengmalm's Owls, Aegolius funereus (Aves, Strigidae) - Máca, Ondřej; Kouba, Marek; Korpimäki, Erkki; González-Solís, David (Frontiers in Veterinary Science, 2021)
Background: Birds act as intermediate or definitive hosts of cyst-forming coccidia parasites of the genus Sarcocystis Lankester, 1882. However, the spectrum of species of Sarcocystis in birds and the role of the latter in the transmission of coccidia are still incomplete for many avian species including Tengmalm’s owl Aegolius funereus (Linnaeus, 1758). During the research of Tengmalm’s owls in Finland, some fledglings were found dead and subsequently parasitologically examined. Therefore, this study is focused on the morphological and molecular description of a Sarcocystis species found in the intestine of the Tengmalm’s owl and its possible role as a definitive host. Methods: Eleven fledgling owls in the Kauhava region of west-central Finland were found dead and subsequently were submitted for necropsy, parasitologically examined through the flotation-centrifugation coprological technique for the presence of oocysts/sporocysts of genus Sarcocystis by light microscopy. Wet mounts were used for the examination of muscle samples (breast, legs, heart). Polymerase chain reaction and nested-PCR were carried out by using primers for 18S rRNA, 28S rRNA, ITS1 region, and CO1 genes. Results: All eleven examined owls were parasitized by numerous sporocysts and oocysts in the intestinal mucosa scrapings (prevalence 100%). Sporulated oocysts and sporocysts measured 16.34−16.96 × 11.47−12.09 µm and 11.85−13.52 × 7.77−9.25 µm, respectively. Skeletal and heart muscles were negative for sarcocysts. Sarcocystis sp. ex Aegolius funereus (hereafter Sarcocystis sp. Af) is closely related to Sarcocystis strixi in the barred owl (Strix varia Barton, 1799) from the USA and Sarcocystis sp. isolate 5 in the European shrew (Sorex araneus Linnaeus, 1758) from the Czech Republic. The phylogenetic analysis allowed to determine the relationship of the herein reported Sarcocystis sp. with its congeners. Conclusions: This work provided the first and most comprehensive record on Sarcocystis from owls obtained in Finland, thus highlighting the importance of molecular data in species identification.